Influence of the application of silicon on the physiological and biometric characterists of maize cultivars under water stress - Bianchini, Hudson Carvalho (2019)
Maize is a crop known to be highly sensitive to water stress. When water becomes a limiting factor, the water potential and the water content of the plants are substantially reduced. Under these conditions, exogenous application of Si can substantially improve water use efficiency, photosynthetic rate and yield in maize plants. The objective of this work was to evaluate calcium silicate efficiency as a water stress reducer in two maize cultivars. Two experiments were conducted, the first using cv. BR-1010, (sensitive to water stress) and the second using cv. DKB-390 (tolerant to water stress). The experiments were organized in a completely randomized design, in four replicates, with two doses of calcium silicate: 0 % (absence) and 100 % (presence) of calcium silicate indicated in the calculation of soil liming, and two irrigation blades: 30 and 100 % water replacement, determined according to the soil water retention curve, in four replicates. In each experiment, the parameters evaluated were gas exchange, net photosynthetic rate, transpiration rate, stomatal conductance, putrescine content, leaf contentes of Ca, K, Zn and Fe quantification by neutron activation, dry matter production on leaves and stem, weight of 1000 seeds and crop yield. It was concluded that two maize cultivars studied, cv. BRS-1010 (water stress sensitive) and DKB-390 (water stress tolerant) showed higher dry matter production on leaves and stem, higher weight of 100 seeds and higher crop yield in the presence of calcium silicate. The content of putrescina increased in plants submitted to water restriction. The leaf contents of Ca, K, Zn and Fe varied according to the cultivars and water blade studied. Calcium silicate favored a greater efficiency in the use of water under conditions of low water availability, using 30 % irrigation blade. In cv. DKB 390, the application of calcium silicate favored an increase in the net photosynthetic rate, transpiration rate, stomatal conductance.